Identification of an assembly domain in the small subunit of ribulose-1,5-bisphosphate carboxylase. - Wasmann, C C (1989)
The mature small subunit (SSU) of ribulose-1,5-bisphosphate carboxylase/oxygenase (EC 4.1.1.39) in higher plants contains a highly conserved sequence of 16 amino acids that is absent in the SSUs of cyanobacteria. To determine whether this region of the SSU of higher plants has a specific function, portions of the SSU genes (rbcS) of pea (Pisum sativum) and the cyanobacterium Anacystis nidulans were fused to create chimeric genes that either lacked or contained the coding sequence for the 16 conserved amino acids. Precursor proteins synthesized in vitro from the chimeric genes were incubated with isolated pea chloroplasts to assay import and assembly into the holoenzyme. Fusion proteins lacking the 16-amino acid sequence were imported and processed but failed to assemble with endogenous large subunit. Addition of the region from a pea rbcS containing the 16 amino acids to the rbcS of Anacystis enabled the imported SSU fusion protein to assemble with pea large subunit. This 16-amino acid sequence is encoded by a separate exon in certain rbcS genes of higher plants. We propose that the conserved 16-amino acid sequence constitutes a domain acquired to facilitate assembly of the eukaryotic holoenzyme.